1997
DOI: 10.1076/ejom.35.2.69.13065
|View full text |Cite
|
Sign up to set email alerts
|

Avian Gastrulation and Neurulation Are Not Impaired by the Removal of the Marginal Zone at the Unincubated Blastoderm Stage

Abstract: In the present study, we removed the whole area marginalis, Rauber's sickle and the peripheral part of the area centralis from unincubated chicken blastoderms (st IV, Vakaet, 1962a). By placing a fragment of a quail Rauber's sickle (functioning as early gastrulation organizer: Callebaut and Van Nueten, 1994) at different places and oriented in different directions on the remaining central part of the area centralis, we observed, after in vitro culture, a normal embryonic development. This indicates that the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In all our experimental studies, we have always observed a strong PS-inducing effect by Rauber's sickle, even in the total absence of the caudal marginal zone (Callebaut et al, 1997). After transplantation of quail caudal marginal zones or upper layer fragments taken from above Rauber's sickle on the cranial quadrants or anti-sickles of whole unincubated chicken blastoderms, we could not observe induction phenomena (Callebaut et al, 1998).…”
Section: Rauber's Sickle and Not The Caudal Marginal Zone Initiates Pmentioning
confidence: 54%
See 1 more Smart Citation
“…In all our experimental studies, we have always observed a strong PS-inducing effect by Rauber's sickle, even in the total absence of the caudal marginal zone (Callebaut et al, 1997). After transplantation of quail caudal marginal zones or upper layer fragments taken from above Rauber's sickle on the cranial quadrants or anti-sickles of whole unincubated chicken blastoderms, we could not observe induction phenomena (Callebaut et al, 1998).…”
Section: Rauber's Sickle and Not The Caudal Marginal Zone Initiates Pmentioning
confidence: 54%
“…The latter is known to induce prosencephalon-like structures (Pera and Kessel, 1997). By interaction with sickle endoblast arising from Rauber's sickle (the early gastrulation organizer: Callebaut and Van Nueten, 1994;Callebaut et al, 1997) or from Hensen's node (a later avian organizer: Waddington, 1932), endophyll orients or re-orients the head region and the caudocranial direction of an induced miniature embryo (Callebaut et al, 1999). Chapman et al (2003) suggest that successive inductive interactions between primary hypoblast, anterior definitive endoderm and epiblast act to promote an anterior character.…”
Section: Endophyllmentioning
confidence: 99%
“…This inductive capacity exists broadly in the posterior marginal zone at stage X but becomes more restricted to the posterior-most marginal zone by stage XII (Eyal-Giladi and Khaner, 1989;Khaner, 1995). Detailed studies of the posterior marginal zone have mapped its inductive activity to nonepiblast midline cells immediately posterior to Koller's sickle (Bachvarova et al, 1998) rather than cells of the Koller's sickle itself or hypoblast cells as previously thought (Azar and Eyal-Giladi, 1979;Eyal-Giladi et al, 1992Callebaut et al, 1997). These studies indicate that all epiblast cells are competent to respond to the inductive cues provided by the posterior midline cells and can undergo primitive streak formation.…”
Section: Induction Of the Initial Primitive Streakmentioning
confidence: 95%
“…When a segment of the posterior marginal zone of the blastodisc is implanted into an anterolateral marginal zone, an ectopic primitive streak is induced ( Fig. 3A-C; Khaner and Eyal-Giladi, 1986;Izpisua-Belmonte et al, 1993;Callebaut and van Nueten, 1994;Callebaut et al, 1997). This inductive capacity exists broadly in the posterior marginal zone at stage X but becomes more restricted to the posterior-most marginal zone by stage XII (Eyal-Giladi and Khaner, 1989;Khaner, 1995).…”
Section: Induction Of the Initial Primitive Streakmentioning
confidence: 99%
See 1 more Smart Citation